2012
DOI: 10.1146/annurev-med-042910-135833
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: New Insights in Pathogenesis and Novel Therapeutics

Abstract: Concepts of multiple sclerosis (MS) have shifted from the traditional view of a T cell-mediated, demyelinating disease of the white matter to include a broad range of immunopathogenic mechanisms, axonal damage, and widespread gray matter pathology. The cause of MS remains unknown, but recent epidemiological work has focused on genetic factors; environmental factors such as vitamin D, sunlight, and Epstein-Barr virus; and the controversial theory of chronic cerebrospinal venous insufficiency. Revised criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 88 publications
0
50
0
Order By: Relevance
“…These studies attributed the findings to the level of exposure to sun light and vitamin D intake through diet, demonstrating a clear association between vitamin D-deficiency and risk of MS development [15,[23][24][25]. Many of these studies suggested that lower serum vitamin D levels could be predictive of higher incidence of relapses among MS patients [11,[26][27][28].…”
Section: Risk Factorsmentioning
confidence: 99%
“…These studies attributed the findings to the level of exposure to sun light and vitamin D intake through diet, demonstrating a clear association between vitamin D-deficiency and risk of MS development [15,[23][24][25]. Many of these studies suggested that lower serum vitamin D levels could be predictive of higher incidence of relapses among MS patients [11,[26][27][28].…”
Section: Risk Factorsmentioning
confidence: 99%
“…85,169 In particular, a specific subset of T helper cells (Th-17) has been identified to be the leading cause of multiple sclerosis, because they secrete interleukin-17 and are endowed with an ability to open the blood-brain barrier, thereby driving the neuronal insult. 86 In addition, the immune attack towards myelin is boosted by recruitment of T cells from the periphery and activation of antibody-secreting B cells by reactive T cells, culminating in an assault on myelin, followed by demyelination. 87,88 Based on severity of symptoms, multiple sclerosis is classified into four subtypes.…”
Section: T Cell Infiltration In Multiple Sclerosismentioning
confidence: 99%
“…In the initial stages of the disease, before lymphoid neogenesis occurs and tertiary lymphoid structures within the meningeal compartment are able to sustain a continuous inflammatory process [69], these interactions probably take place in CLNs [3] and are dependent on CNS antigen transport to those sites [57]. So, CLNs may act as loci of antigen presentation and T-or B-lymphocyte priming [54] but also as sites of tolerance induction towards CNS antigens [70,71].…”
Section: The Hydrostatic Approachmentioning
confidence: 99%
“…Both genetic and environmental factors have been implicated in the pathogenesis [2]. The precise cause remains largely unknown, but there is evidence of a myelin-antigen-specific, Th1-mediated immune process resulting in macrophage-mediated demyelination, axonal loss and gliosis [3].…”
Section: Introductionmentioning
confidence: 99%